Endophyte-engineered plant immunity: A post-GMO strategy for programmable crop defense - Fan Zhang; Jing Zheng; Xinyun Xie; Mengru Tang; Hongyang Li; Linyin Zuo; Lu Zheng; Hao Liu; Junbin Huang; Zhinan Mei; Xiao-Lin Chen (Molecular Plant, 2026)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Disentangling wavy and vortical motions in concurrent snapshots of the sea surface height and velocity - Chuanyin Wang; Zhiyu Liu; Hongyang Lin; Cesar Rocha; Qinghua Yang; Dake Chen; Junbin Gong (Ocean Modelling, 2025)

A high-performance flexible coaxial BTO/PAN piezoelectric nanofibers for facial expression analysis - Junfei Lin; Junbin Yu; Fangyuan Chen; Xuying Jia; Jiahe Li; Juanhong Zhao; Jian He; Xiaojuan Hou; Jiliang Mu; Xiujian Chou (Chemical Engineering Journal, 2025)

Metatranscriptomics provides an in-depth perspective on the resistance and detoxification of anammox bacteria to dissolved oxygen in a pilot CANON process - Huaihao Xu; Xiaojun Wang; Mingyuan Wang; Junbin Wu; Bo Zhang; Jinsong Wang; Qiuting Zhang; Bingrong Lin; Shaohua Chen (Water Research, 2025)

Strategic small molecule engineering: Unleashing the full potential of Kevlar aramid membrane in organic solvent nanofiltration - Yanqing Xu; Jiaqi Xiong; Qite Qiu; Chenfei Lin; Junbin Liao; Huiming Ruan; Jiangnan Shen (Chemical Engineering Journal, 2024)

Constructed wetland treating mine drainage wastewater: Performance and microbial mechanisms - Xiaoyong Zhong; Xindong Teng; Bo Tang; Xunan Lin; Junbin Chen; Ronghua Zhao; Qiang Wu; Xiao Huang (Journal of Water Process Engineering, 2024)

Enriched Environment Inhibits Neurotoxic Reactive Astrocytes via JAK2-STAT3 to Promote Glutamatergic Synaptogenesis and Cognitive Improvement in Chronic Cerebral Hypoperfusion Rats - Bin Fan; Junbin Lin; Qihang Luo; Weijing Liao; Chizi Hao (Neurotoxicity Research, 2024)

Pig eye area temperature extraction algorithm based on registered images - Bin Zhang; Deqin Xiao; Junbin Liu; Senpeng Huang; Yigui Huang; Tanyu Lin (Computers and Electronics in Agriculture, 2024)

The resting-state topological organization damage of language-related brain regions in post-stroke cognitive impairment - Sirui Wang; Bo Rao; Guofu Miao; Xin Zhang; Jun Zheng; Junbin Lin; Minhua Yu; Xiaoli Zhou; Haibo Xu; Weijing Liao (Brain Imaging and Behavior, 2022)

Insecticide resistance and its underlying synergism in field populations of Spodoptera frugiperda (J. E. Smith) from Hainan Island, China - Junbin Liu; Zheng Hao; Shengyuan Yang; Yuying Lin; Hao Zhong; Tao Jin (Phytoparasitica, 2022)

Perilipin LDP1 coordinates lipid droplets formation and utilization for appressorium‐mediated infection in Magnaporthe oryzae - Xuan Cai; Jingjing Yan; Caiyun Liu; Junjie Xing; Zhiyong Ren; Ahmed Hendy; Lu Zheng; Junbin Huang; Xiao‐Lin Chen (Environmental Microbiology, 2020)
Summary Lipid droplets (LDs) serve as one of the major reservoirs in conidia of Magnaporthe oryzae and are quickly utilized during appressorium formation. Here, we identified a gene, LDP1 , encoding a perilipin that is important for LD formation and utilization during appressorium maturation. LDP1 is highly expressed in conidium and immature appressorium. Disruption mutants of LDP1 were significantly reduced in virulence, due to appressorial turgor reduction and difficulty in penetration. LDs were significantly reduced in the Δ ldp1 mutant, indicating LDP1 was required for LDs formation. LDP1 was colocalized with the LDs in conidium and immature appressorium but was gradually separated during appressorium maturation. A typical intracellular triacylglycerol lipase, TGL1‐2, was clearly separated with LDs in conidium and immature appressorium but was well colocalized with LDs during appressorium maturation. The subcellular localization of TGL1‐2 was affected by LDP1. These data suggested that LDP1 was bound to LDs for protecting from utilization in conidia and at the early appressorium stage but was separated from LDs for lipase entering and degradation. LDP1 was phosphorylated by CPKA at Thr96, which was essential for its localization and functions. These data indicate perilipin LDP1 can coordinate LD formation and utilization for appressorium‐mediated infection of M . oryzae .

Graph-Cut-Based Segmentation of Proximal Femur from Computed Tomography Images with Shape Prior - Junbin Huang; James F. Griffith; Defeng Wang; Lin Shi (Journal of Medical and Biological Engineering, 2015)